The Liberal Dilemma: Balancing Security and Freedom in Public Risk Management - Abdullah Demirel (Liberal Düşünce Dergisi, 2026)
This study examines the tension between risk management in public administration and individual freedoms from a liberal perspective. As state intervention expands across crisis domains, conflicts arise between public security and fundamental rights. Adopting a qualitative comparative approach, the research analyzes risk governance in health, economy, environment, disaster management, and technology, using Türkiye, the US, the EU, and South Korea as cases. The framework focuses on policy instruments, effects on negative and positive liberty, and the principles of proportionality, transparency, participation, and temporariness. Findings show a dual impact: restrictive measures may curtail negative liberty, while social protections and public services can enhance positive liberty. The study concludes that legitimate risk governance in liberal democracies requires a balance between state intervention and individual autonomy, guided by proportionality, transparency, participation, and temporal limitation.